Global biomass potentials under sustainability restrictions defined by the European Renewable Energy Directive 2009/28/EC. Issue 6 (10th January 2013) - Schueler, Vivian; Weddige, Ulf; Beringer, Tim; Gamba, Liliana; Lamers, Patrick
Abstract: The political will to reduce global GHG emissions has largely contributed to increased global biofuel production and trade. The expanding cultivation of energy crops may drive changes in the terrestrial ecosystems such as land cover and biodiversity loss. When biomass replaces fossil energy carriers, sustainability criteria are therefore crucial to avoid adverse impacts and ensure a net positive GHG balance. The European Union has set mandatory sustainability criteria for liquid biofuels in its Renewable Energy Directive (RED) 2009/28/EC to ensure net positive impacts of its biofuel policy. The adoption of sustainability criteria in other world regions and their extension to solid and gaseous biomass in the EU is ongoing. This paper examines the effect of the EU RED sustainability criteria on the availability of biomass resources at global and regional scale. It quantifies the relevance of sustainability criteria in biomass resource assessments taking into account the criteria's spatial distribution. This assessment does not include agricultural and forestry residues and aquatic biomass. Previously unknown interrelations between sustainability criteria are examined and described for ten world regions. The analysis concludes that roughly 10% (98.5 EJ) of the total theoretical potential of 977.2 EJ occurs in areas free of sustainability concerns.